TINDAK TUTUR IMPERATIF GURU DALAM PROSES BELAJAR MENGAJAR SMA/SMK KECAMATAN OEBOBO, KOTA KUPANG - Ahmad Ahmad (Jurnal Muara Pendidikan, 2020)
This research aims to examine the teacher's imperative speech acts in the teaching and learning process of Muhammadiyah High School Kupang, State High School 5 Kupang, Citra Bangsa Christian High School, Muhammadiyah Vocational School Kupang, and State Vocational School 1 Kupang. This type of research is descriptive qualitative. The data in this reserch are in the form of speech that shows the form and meaning of imperative speech acts. Data collection techniques are carried out through the technique of observed free conversation, recording techniques, and note taking techniques. The results of the research show that: there are four forms of imperative teacher speech acts, namely (1) direct literal imperative speech acts, (2) imperative speech acts not literal, (3) indirect literal imperative speech acts, (4) indirect imperative speech acts not literal. Ten meanings of imperative speech act (1) Speech acts that contain imperative meanings of commands, (2) Speech actions that contain imperative orders of messengers, (3) Speech actions that contain imperative demand. (4) Speech actions that contain imperative meaning of courtesy, (5) Speech actions that contain imperative meaning of invitation, (6) Speech actions that contain imperative meaning of appeal, (7) Speech actions that contain imperative prohibition, (8) Speech actions that contain the imperative meaning of the request, (9) speech acts that contain the imperative meaning of insistence, and (10) speech acts that contain the imperative meaning of persuasion.